Importance of forearc topography for the triggering of aftershocks of megathrust earthquakes: insights from mechanical models and the Tohoku-Oki and Maule earthquakes - A. Dielforder; A. Dielforder; G. M. Bocchini; A. Hampel (Solid Earth)
Aftershocks of megathrust earthquakes at subduction zones may be driven by stresses arising from the topography of the forearc. However, the effect of topographic stresses on aftershock triggering is quantitatively not well understood and has been neglected in Coulomb failure stress models that assess whether the stress change caused by an earthquake promotes or inhibits failure on nearby faults. Here we use analytical and numerical models to examine the importance of topographic stresses on Coulomb failure stress changes caused by megathrust earthquakes. We show that topographic stresses are a prerequisite for widespread aftershock seismicity in the forearc and that their superposition with tectonic stresses leads to a dependence of the forearc stability on the stress state before and after the earthquake. The dependence can be taken into account by determining the Coulomb failure stress change between optimal failure planes before and after the earthquake, which requires constraining the total stresses in the forearc. Applying our modelling approach to the 2011 Mw 9.0 Tohoku-Oki and 2010 Mw 8.8 Maule megathrust earthquakes yields coseismic Coulomb failure stress changes of up to ∼40 MPa, which promoted the majority of aftershocks in the Japanese and Chilean forearcs. The model results further reveal that the spatial distribution of aftershocks was not only influenced by the megathrust stress drop and the proximity of faults to failure but also by local differences in forearc topography and pre-earthquake stress state. Our analysis highlights the significance of total stresses in Coulomb failure stress calculations, enabling a better estimation of seismic hazard at subduction zones.